SIGHAT IJAB KABUL TRANSAKSI JUAL BELI: PERSPEKTIF ULAMA KALIMANTAN SELATAN (ANALISIS PRAKTIK BERMAZHAB DI KALIMANTAN SELATAN) - Sa'adah, Hj. Rusdiyah, Zainal Muttaqin, (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2015)
Ulama(Islamic Scholars) who obligatetheconsentandagreement (shigat) in the form ofspeechgrantedbycertain wordssuch as"buying and selling" indicates that those ulamaare from Syafi'iyyahschool of thought with qaulypattern.sect. Theulama'who require the obligationof shigatbut withno certain words as above, is saidtobe in the school of thought with manhajypattern. Theulama'who does not obligate the saying of (shigat) is not Syafi'iyyahoriented,and is not tied toa particular school of thought. In the context ofshigat, these ulamaarguebased onscholarly opinionsstatingthat the transactionwithoutshigatis considered valid, and this transactionis calledBa'ial-mu'atah.